Psychological Diagnostics Of Destructive Motivation Of Personnel - Gyulambaryan, Nona (Զանգակ հրատ.)
The social development of a person is emphasized by the formation of social forms of behavior, which are changed in the process of socialization of a person. The main factor in the development of a person's social behavior is activity, in particular, professional activity, during which a person acquires not only professional skills but also learns communicative and socially significant norms and rules of behavior. In the course of professional activity, the ability to respond to the work and behavioral requirements of the employer is gradually formed. Of course, the motivational component of a person's behavior undergoes an inevitable change due to work activity. This article presents the key elements of psychological diagnostics of the destructive motivation of personnel. There are presented statistically significant correlations between variables of motivation for success and to avoid failures.
Keywords: Pedagogy; Psychology